2016
DOI: 10.1002/smll.201601443
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Superhydrophobic Highly Transmissive Films for Optical Applications

Abstract: Inspired by the transparent hair layer on water plants Salvinia and Pistia, superhydrophobic flexible thin films, applicable as transparent coatings for optoelectronic devices, are introduced. Thin polymeric nanofur films are fabricated using a highly scalable hot pulling technique, in which heated sandblasted steel plates are used to create a dense layer of nano- and microhairs surrounding microcavities on a polymer surface. The superhydrophobic nanofur surface exhibits water contact angles of 166 ± 6°, slidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…2a495051. Hot pulling is a modified hot embossing process, in which demolding forces occurring during polymer and mold insert separation are used to fabricate high aspect ratio polymeric nano- and microstructures525354.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a495051. Hot pulling is a modified hot embossing process, in which demolding forces occurring during polymer and mold insert separation are used to fabricate high aspect ratio polymeric nano- and microstructures525354.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent mold retraction (0.3 mm/min) results in formation of dense nano- and microhairs. Samples used for oil/water filtration and hydrophobic recovery experiments were fabricated using a modified hot pulling technique in which initial PC films were attached to a sacrificial cyclo-olefin-copolymer layer51. Polymers used for nanofur fabrication include PC (Makrolon LED2045, Bayer, Germany); PLA (Uhde Inventa-Fischer GmbH, Germany); PET films (Hanita Coatings, Israel); PP, LDPE, HPDE films (Infiana, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…[28,29] Recently,s ilane and polymers were used to achieve high hydrophobicity.F or instance, Vüllers et al constructed nanohairs on polycarbonatef ilm by hot pulling. [30] Mates et al developed aw ater-based and fluorine-free superhydrophobic formulation by using environmentally safe constituents:T iO 2 NPs andp olyolefin copolymers. [31] The hydrolysis of silane and polymer, together with spray coating, also provideafluorinefree, substrate-independent, and mechanically durable strategy for superhydrophobic coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Vullers et al [104] reported a facile and efficient technique to produce superhydrophobic flexible thin films that are applicable as transparent coatings for optoelectronic devices. They fabricated a thin polymeric nanofur from optical-grade polycarbonate (PC) using a two-step fabrication process, comprised of hot embossing and hot pulling steps, as shown in Figure 11a,b.…”
Section: Hot Pulling Techniquementioning
confidence: 99%
“…With an aim on transparent, flexible, and self-cleaning properties, superhydrophobic surfaces have also been developed for eyeglasses and sunglasses. Possessing the properties of self-cleaning and optical transparency, a thin, flexible polymeric film could be applied for light management applications and it is attractive for commercial applications in optoelectronic devices [104]. Highly-flexible superhydrophobic thin film can be used for closed-end tubes and several uneven complex geometries [105].…”
Section: Applications Of Transparent and Flexible Superamphiphobic Sumentioning
confidence: 99%